Aluminum and its role as a recyclable, sustainable carrier of renewable energy. (1st October 2020) - Trowell, K.A.; Goroshin, S.; Frost, D.L.; Bergthorson, J.M.
Graphical abstract: Highlights: Aluminum is a promising mechanism for the commodification of renewable energy. The cycle efficiency of aluminum fuel outperforms both green hydrogen and ammonia . Electricity prices below $26/MWh make aluminum competitive with a $50 barrel of oil. Abstract: An energy system completely reliant on renewables requires an energy carrier to mitigate the geographic and seasonal variability of such resources. The cost of renewable electricity is now below the cost of hydrocarbon-generated electricity, and low enough that it is economically sensible to produce fuels using renewable electricity (Power-to-X). Aluminum is well suited to play the role of "X" in a power-to-X system. Aluminum possesses the characteristics that are most important for a sustainable energy carrier: high energy density, abundance, recyclability, and it is anticipated that the alumina-reduction process will soon be free of carbon emissions. Oxidation of aluminum yields a cycle efficiency of approximately 25% if the product(s) of oxidation are used to power a heat engine with an efficiency of 40%. This compares favourably to other proposed energy carriers, such as hydrogen and ammonia. These fuels yield cycle efficiencies of no more than 23% and 18% respectively, if the carbon-free production route is used to produce the hydrogen and ammonia. Aluminum fuel can be competitive with a $50 barrel of oil if the reduction process is powered by electricity priced at $26/MWh or less.